Role Of Media Influencing Investor’s Investment Decision - Gnanakkan, J. Moses; Sheba, M. Surath (International Journal of Psychosocial Rehabilitation, 2020)
In order to assess how the role of media influences investor’s investment decisions, a survey was administered to N=567 to investors working in the IT sector in Chennai city. The survey was administered through a questionnaire and with questions related to the influence of media towards individual investments in equity. The Analysis confirmed that there is a difference between gender, age and income of investors and the role of media, as well as the investment profile of the amount invested by investors, their experience and average returns earned by them and the role of media.